Conservative Management of Chylous Ascites Following Endometrial Cancer Staging - Fırat Tülek; Salih Taşkın; Korhan Kahraman; Fırat Ortaç (Medical Network, 2012)
To present a case of chylous ascites after staging surgery for endometrial carcinoma A 57 years old postmenopausal woman was operated for endometrial cancer, chylous ascites developed after this surgery. Chylous ascites was treated conservatively include low fat diet and medium chained triglyceride parenterally. Chylous ascites may be successfully managed with conservative approach without surgical intervention.